Scalp metastases of glioblastoma multiforme: Case report - (:unkn) unknown (My University, 2007)
Glioblastoma multiforme is an aggressive neoplasm of the central nervous system and skin metastases are extremely rare. In this article, a patient who had rapidly developing scalp masses after surgery for glioblastoma multiforme is presented. The metastatic masses with ulceration were disturbing for the patient and his family, so he was operated on for palliative resection of the tumor. The resulting extensive defect was reconstructed with a free latissimus dorsi flap. Healing phase was uneventful and he was discharged from the hospital on the ninth postoperative day. A palliative surgery, even if it may necessitate a complex reconstruction, can be recommended in specific cases to improve quality of life and to ease patient care. © Springer-Verlag 2006.
Keywords: Free flap reconstruction; GBM; Glioblastoma multiforme; Scalp metastases